O papel do performer da interpretação de duas obras contemporâneas para violoncelo: For cello, de Jocy de Oliveira e Para os que ficam, de Nathalia Fragoso - Daniel Menezes Ludolf Tamietti (2023)
This work presents the learning process of two contemporary pieces for cello and electronics with the aim of discussing the role of the performer in their interpretation. Initially, some theoretical foundations are presented, such as the concept of work by Lydia Goehr, the view of the score as a script by Nicholas Cook, reflections on musical notation and the determined or indeterminate elements contained in it, reflections on creativity in music (and in performance) and about the composer/performer relationship. With these ideas in mind, two case studies were carried out, which consisted of the preparation and performance of two pieces with different characteristics. The chosen pieces were For Cello (1994) by Jocy de Oliveira and For those who remain (2022-2023) by Nathalia Fragoso, both for cello and electronics. The first is a score that presents more conventional elements such as pentagram, defined notes and proportional notation. The second, a graphic/textual score that includes an electronic part constructed jointly by the composer and by me, as the work's performer. The learning process of my performances is an important part of the research. It serves to corroborate some of the theoretical foundations presented above and helps to show how the role of the performer is important beyond the mere execution of the score. This process is a creative agent in collaboration with the composer (directly or indirectly) and his decisions can be influenced by several parameters such as notation, environment/context of the performance and the audience.